Breeding habitats of mosquito larvae in a paddy growing area in Kuala Pilah, Negeri Sembilan, Malaysia - Wan-Norafikah, Othman; Chen, Chee Dhang; Mohd-Amir, M.H.; Azahari, Abdul Hadi; Zainal Abidin, A.H.; Nazni, Wasi Ahmad; Mariam, M.; Mohd-Shahizan, J.; Sofian-Azirun, Mohd (Global Science Publications, 2018)
Surveillance of mosquito larvae was performed in a paddy growing area in Kuala Pilah, Negeri Sembilan, Malaysia to uncover different types of breeding receptacles for mosquito larvae and species composition that bred in those positive receptacles. Fifty (50) natural and artificial receptacles were positive with mosquito breeding. About 96.00% of these positive receptacles were found outdoor. All positive indoor and most positive outdoor receptacles were conquered by Aedes albopictus Skuse while the rest were occupied by Culex quinquefasciatus Say. Population dynamics of Ae. albopictus in the study site should be constantly monitored and controlled to avoid the dispersal of mosquito-borne diseases such as dengue and chikungunya among local residents.